Design and development of a multi-winding high-frequency magnetic link for grid integration of residential renewable energy systems. (15th May 2019) - Jafari, Mohammad; Malekjamshidi, Zahra; Zhu, Jianguo
Highlights: Reluctance network modeling, less computation time for magnetic field analysis. Harmonic-based Copper loss analysis is suitable for phase shift converters. Improved modified Steinmetz equation is accurate for core loss analysis. Series coupling tests better than short circuit to measure high leakage inductances. Abstract: Recent advances in magnetic material characteristics and solid-state semiconductors have provided the feasibility of replacing the electrical buses with the high-frequency multi-winding magnetic links in small-scale renewable energy systems. This effectively reduces the number of conversion stages and improves the system's efficiency, cost, and size. Other advantages are galvanic isolation between the ports, bidirectional power flow capability and flexibility in energy management and control. Despite the advantages, design and development of the multi-winding magnetic links is relatively complex and based on computationally expensive numerical methods. Furthermore, the non-sinusoidal nature of voltage and currents, high-frequency parasitic effects and nonlinearity of magnetic material characteristics increase the design complexity. In this paper, the reluctance network modeling as a fast analytical method is used to design a three winding magnetic link. The core and copper losses of the designed component are evaluated taking into account duty ratio, amplitude and phase shift of the non-sinusoidal excitation voltage and currents. The thermal analysis is carried out using an accurate thermal-electric model. A prototype of the magnetic link was developed for application in a residential renewable energy system using amorphous magnetic materials. A set of experimental tests are conducted to measure the electrical parameters, magnetic characteristics, core loss, copper loss and temperature rise of the designed component and the results are compared to the specifications to validate the design procedure.